-4x(1-3)-(2x+2)=-4(5)(1-3)-(2(5)+2)

Simple and best practice solution for -4x(1-3)-(2x+2)=-4(5)(1-3)-(2(5)+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x(1-3)-(2x+2)=-4(5)(1-3)-(2(5)+2) equation:


Simplifying
-4x(1 + -3) + -1(2x + 2) = -4(5)(1 + -3) + -1(2(5) + 2)

Combine like terms: 1 + -3 = -2
-4x(-2) + -1(2x + 2) = -4(5)(1 + -3) + -1(2(5) + 2)

Reorder the terms for easier multiplication:
-4 * -2x + -1(2x + 2) = -4(5)(1 + -3) + -1(2(5) + 2)

Multiply -4 * -2
8x + -1(2x + 2) = -4(5)(1 + -3) + -1(2(5) + 2)

Reorder the terms:
8x + -1(2 + 2x) = -4(5)(1 + -3) + -1(2(5) + 2)
8x + (2 * -1 + 2x * -1) = -4(5)(1 + -3) + -1(2(5) + 2)
8x + (-2 + -2x) = -4(5)(1 + -3) + -1(2(5) + 2)

Reorder the terms:
-2 + 8x + -2x = -4(5)(1 + -3) + -1(2(5) + 2)

Combine like terms: 8x + -2x = 6x
-2 + 6x = -4(5)(1 + -3) + -1(2(5) + 2)

Combine like terms: 1 + -3 = -2
-2 + 6x = -4 * 5(-2) + -1(2(5) + 2)

Multiply -4 * 5
-2 + 6x = -20 * -2 + -1(2(5) + 2)

Multiply -20 * -2
-2 + 6x = 40 + -1(2(5) + 2)

Multiply 2 * 5
-2 + 6x = 40 + -1(10 + 2)

Combine like terms: 10 + 2 = 12
-2 + 6x = 40 + -1(12)

Multiply -1 * 12
-2 + 6x = 40 + -12

Combine like terms: 40 + -12 = 28
-2 + 6x = 28

Solving
-2 + 6x = 28

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6x = 28 + 2

Combine like terms: -2 + 2 = 0
0 + 6x = 28 + 2
6x = 28 + 2

Combine like terms: 28 + 2 = 30
6x = 30

Divide each side by '6'.
x = 5

Simplifying
x = 5

See similar equations:

| -8+10k+2k=40 | | X-5+2x+9=50 | | 4(-8x+12)=-26-33x | | 13g+9-3f+2-12g= | | (k+4)= | | 2x+9+x-5=50 | | 4b-3-10b-4= | | 6x-4=(-2)x-10 | | 9=m-1+1 | | x^2+27x-124=0 | | 3d-5t+10+t+7d-6= | | 5a+2=5a | | 1.25=-4c+0.25 | | 6w*5w= | | 0.25+0.50t=4 | | 6-(-36)= | | -5(x+7)=4-(-2) | | 5=2x^2+2x | | 9+4h=1-5h | | 4x(7x+3)= | | 28+(2x-1)=3x+22 | | 10+3x+5x=58 | | 4.3=-4+x | | (3b+4g)(3b-4g)= | | Y=x^3-16x | | -29y+5x=17 | | 3y+3=10y+35 | | 4x+8+7=-5x+8-29 | | 2x-102=58-3x | | 4n-9=87 | | -29x+5y=17 | | (-6x+12)+((10x^2)+6x-11)= |

Equations solver categories